Pengaruh Model STAD Terhadap Hasil Belajar Sejarah Siswa SMA Negeri 1 Tuntang - Maisarah, Ersya; Romadi, Romadi (IJTIMAIYA: Journal of Social Science and Teaching, 2025)
Learning outcomes are the abilities that students possess after receiving their learning experiences. However, the learning outcomes of students at SMA Negeri 1 Tuntang are not yet optimal. This study aims to determine the significant differences and effects on student learning outcomes in groups that use the STAD model in teaching history material on the Japanese occupation of Indonesia using a Posttest Only Control Group Design in two classes. The data collection techniques used were observation, tests, questionnaires, and interviews. The results of this study explain the effect of the model, as evidenced by tests that support the hypothesis with the following results: (1) the average posttest score for learning outcomes in the experimental group reached KKTP; (2) the average posttest score of the experimental group was higher than that of the control group; (3) the proportion of posttest score mastery of the experimental group was higher than that of the control group; (4) the significance value was 0.000<0.05 with an effect size of 73.1%. In conclusion, this model has a significant effect on the learning outcomes of the experiment and improves learning outcomes.